2011
DOI: 10.1097/ccm.0b013e318206bf2e
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and reliability of a subcutaneous continuous glucose-monitoring system in critically ill patients*

Abstract: The subcutaneous continuous glucose-monitoring system is reliable for use in critically ill patients and showed glucose values with a strong correlation to arterial reference blood glucose levels, determined by a blood gas analyzer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 26 publications
1
69
2
1
Order By: Relevance
“…During the present study, the proportion of sensor glucose values within 20% of reference glucose was 88% with the enhanced protocol, compared with reported values between 63% and 75% [14][15][16] other than for Brunner et al, 17 who reported a higher percentage of 92%. Most intensive care unit studies evaluated Medtronic (Northridge, CA) sensors, 14,[16][17][18] and only one study evaluated Navigator.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…During the present study, the proportion of sensor glucose values within 20% of reference glucose was 88% with the enhanced protocol, compared with reported values between 63% and 75% [14][15][16] other than for Brunner et al, 17 who reported a higher percentage of 92%. Most intensive care unit studies evaluated Medtronic (Northridge, CA) sensors, 14,[16][17][18] and only one study evaluated Navigator.…”
Section: Discussionmentioning
confidence: 45%
“…Most intensive care unit studies evaluated Medtronic (Northridge, CA) sensors, 14,[16][17][18] and only one study evaluated Navigator. 19 Further improvements in accuracy may be achievable through the intravenous sampling route eliminating or significantly reducing the lag time of 6-15 min reported with subcutaneous sensors.…”
Section: Discussionmentioning
confidence: 99%
“…While few animal studies have been done, the reliability of CGMSs in critically ill patients is an area of active research. The results to date have revealed a strong correlation between arterial reference blood glucose and better performance, compared with point-of-care devices (Corstjens et al 2006;Hoedemaekers et al 2008;Holzinger et al 2009;Brunner et al 2011). These studies pointed out that the accuracy of CGMSs becomes diminished in the hypoglycaemic range.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a larger scale study in 174 critically ill patients revealed a Pearson correlation coefficient of 0.92 when compared to arterial BG levels. Insulin titration error grid analysis to assess the clinical safety of the CGMS demonstrated that more than 99% of determinations were in clinically acceptable zones (Brunner et al 2011). The purpose of using CGMSs is to predict hypo-and hyperglycaemic states, so accurate measurement at the extreme ranges is important.…”
Section: Discussionmentioning
confidence: 99%
“…Others found it useful for reducing hyperglycaemic episodes 35 . The analysis of two prospective randomized trials demonstrated clinically sufficient accuracy and safety 36,37 even in patients on vasopressors 38 . Some reject the use of subcutaneous sensors in the ICU setting 39,40 .…”
Section: Introductionmentioning
confidence: 99%